Primary syphilis with a tongue ulcer mimicking tongue cancer: a case report. Issue 3 (March 2023) - Fukumoto, Chonji; Zama, Manabu; Hyodo, Toshiki; Shiraishi, Ryo; Kamimura, Ryouta; Yagisawa, Shuma; Hasegawa, Tomonori; Komiyama, Yuske; Izumi, Sayaka; Wakui, Takahiro; Kawamata, Hitoshi
The main symptom in primary syphilis is a small, painless, sore or ulcer called a chancre on the penis, vagina, or around the anus, although chancres can sometimes appear in the mouth or on the lips, fingers, or buttocks. We present the case of a man in his early 60 s with a chief complaint of a painful tongue ulcer. An ulcerated, indurated, and hemorrhagic lesion (23 × 14 mm) was found on the ventral tongue surface, near the oral floor. Palpation identified several swollen, mobile, elastic cervical lymph nodes, with no tenderness. We initially diagnosed tongue cancer; however, during a subsequent detailed examination for a malignant tumor, including biopsy and obtaining additional history, his disease was finally identified as primary syphilis with multiple swollen cervical lymph nodes. Oral amoxicillin and probenecid were started, and after 14 days, there was partial reduction in the size of the submandibular lymph nodes and the ulcer on the left tongue margin. The number of patients with syphilis in Japan increased by eight times from 2012 to 2018. We suggest that dentists consider primary syphilis as a differential diagnosis for oral refractory ulcer with induration and obtain a detailed patient history.